Effects of train load and water on stress intensity factors of the crack in slab track. (13th September 2021) - Cui, Xuhao; Zhou, Rui; Guo, Gaoran; Du, Bowen; Liu, Hanlin
Highlights: A 3D finite element model of the CRTS II slab track with a crack was established. The stress intensity factors at the crack tip were calculated. The effects of the train load and water on the stress intensity factors of the crack were analyzed. Abstract: The crack in the slab track is a major problem for the operation of the China Railway Track System (CRTS) II slab track. This problem is serious in areas with abundant rainwater and poor drainage. To investigate the effects of the train load and water on the crack damage of the slab track, a three-dimensional (3D) finite element (FE) model of a slab track with a crack was established based on fluid–structure interaction theory. The effects of the train load (e.g. speed, axle load) and water on the crack were analyzed. The results indicate that the stress intensity factors (SIFs) at the crack tip are increased owing to the effect of the train load, resulting in a tendency of cracking in the sliding or scissoring shear mode. The SIFs at the crack tip increase with an increase in the train speed and axle load. The hydrodynamic pressure of the water in the crack below the rail is the largest when the crack in the track slab is filled with water, and the hydrodynamic pressure increases with an increase both in the train speed and axle load. However, the effect of water on the SIFs of the crack is not evident.